Encephalographic Study of Headache - Arellano Z., Alejandro P. (1963)
In 500 patients with 168 EEGs were selected ; because they had major headache. In 40 they had with certain organic disease , 33 patients with epilepsy, and the remaining 95 with headache no demonstrable organic cause . This last group is mainly analyzed , and subdivided into banal headache 44 cases , atypical 34 cases migraine and typical migraine 17 cases , the percentage of abnormality in EEG based on each group is as follows : a) banal headache 36.3 % b ) atypical migraine 58.8 % c) 58.8 % The typical migraine overall percentage of electroencephalographic abnormality based on the total group is 48.4 % against 51.6 % in normal EEGs . The major abnormality is characterized by hipervoltaje , theta waves and synchronous e hypersynchronous paroxysmal slow , and asymmetry of the occipital alpha activity. Asynchrony is also moderate . It was also found asymmetry of the anterior frontal beta activity in 4 cases of migraine. "Financial centroencefálico headache " and " migraine centrencephalic " arises . EEG abnormalities percentages presented with headache and epileptic organic frames equally . In conclusion, the comprehensive clinical evaluation of patients with headache is essential electroencephalographic study and banal distinction of typical or atypical headache or migraine centroencefálicas.